Model of adoption of virtual tools by university students in the context of an emerging economy - López-Sánchez, Jerri Alejandro; Patiño-Vanegas, Juan Camilo; Valencia-Arias, Alejandro; Rojas Coronel, Angel Marcelo (Frontiers in Education, 2024)
The impact of COVID-19 on higher education has generated the need to resignify teaching processes, motivation, and the development of new knowledge, linking information and communication technologies (ICT) as pedagogical tools. Understanding this reality fosters innovative spaces and opportunities for student cooperation and participation. Therefore, the objective of this article is to examine the level of adoption of virtual tools by students attending higher education institutions in Medellín. For this study, a sample of 373 students was used using the quantitative approach with a descriptive scope using factor analysis statistical techniques through SPSS software. This allowed establishing the associative degree of the variables and the hypotheses with the constructs of the technology acceptance model (TAM). Finding that the strongest relationships are ease of use and perceived usefulness and demonstrating that technological devices such as laptops and smartphones are perceived as useful for use in training processes by students, they will develop a positive attitude towards their use. This plays a key role in determining students' perceptions about the use and adoption of ICT tools oriented to teaching-learning, as well as for the design of effective pedagogical strategies in crisis situations.